The Sunshine Hotel/Charlie's Story
The DVD contains 2 radio documentaries: “The Sunshine Hotel” and “Charlie’s Story.” The first documentary is an audio portrait of the Sunshine Hotel, one of the final vestiges of Bowery (New York's notorious skid row) and one of the last of the no-frills establishments. The second story belongs to Charlie Geter, a man who had been living in the Palace Hotel, a flophouse on New York City's Bowery, for over twenty-five years. Producers David Isay and Stacy Abramson met Charlie while they were working on their documentary “The Sunshine Hotel” and impressed by Charlie's personality, they gave him a tape recorder and asked him to interview other residents of the Palace Hotel and to tell his life story.